A linearized approach for the seismic response analysis of flexible cable net structures. Issue 88 (September 2016) - Xiang, Yang; Luo, Yongfeng; Guo, Xiaonong; Xiong, Zhe; Shen, Zuyan
Abstract: Cable net structures are characterized by significant geometrical nonlinear properties. The linear modal superposition method (LMSM), which ignores the effect of nonlinearity, is believed not suitable for the seismic response analysis of this kind of structures. To conquer the drawback of LMSM, a non-iterative linearization method (NILM) is proposed in this paper. An energy parameter named the "stiffness parameter" is utilized in generating the nonlinear equivalent single degree of freedom (ESDF) systems for the dominant vibration modes of cable nets. The nonlinear stiffness of an ESDF system is simulated by a quadratic function about the equivalent displacement. Based on a stochastic linearization process, the relationship between the equivalent linear stiffness and the displacement response of a modal ESDF system is established. Then the structural responses are computed according to the design response spectra through a non-iterative procedure. Finally, the effectiveness of the proposed NILM is illustrated by a numerical example that carried out on a trapezoid-shaped cable net supported curtain wall structure. It is demonstrated that the proposed NILM, which takes the stiffness hardening effect into consideration, could not only yield better results than the LMSM does, but also exhibit satisfying timesaving property over the nonlinear RHA. Highlights: An energy parameter is used to describe the nonlinear properties of structures. A cable net exhibits the same nonlinear property as a Duffing system does. The "equivalent linear stiffness"-"peak displacement" relationship is deviated. The nonlinear responses are computed directly based on the linear response spectra. The proposed method is more effective than the linear modal superposition method.